unr, a cellular cytoplasmic RNA-binding protein with five cold-shock domains, is required for internal initiation of translation of human rhinovirus RNA - Hunt, Sarah L. (Cold Spring Harbor Laboratory Press, 1999)
Initiation of translation of the animal picornavirus RNAs occurs via a mechanism of direct ribosome entry, which requires a segment of the 5′ UTR of the RNA, known as the internal ribosome entry site (IRES). In addition, translation of the enterovirus and rhinovirus (HRV) subgroups requires cellular trans-acting factors that are absent from, or limiting in rabbit reticulocytes, but are more abundant in HeLa cell extracts. It has been shown previously that HeLa cells contain two separable activities, each of which independently stimulates HRV IRES-dependent translation when used to supplement reticulocyte lysate; one of these activities was identified as polypyrimidine tract-binding protein (PTB). Here, the purification of the second activity is achieved by use of an RNA-affinity column based on the HRV 5′ UTR. It comprises two components: a 38-kD protein (p38), which is a novel member of the GH–WD repeat protein family and has no intrinsic RNA-binding activity; and a 96- to 97-kD protein doublet, which was identified as unr, an RNA-binding protein with five cold-shock domains. Coimmunoprecipitation with antibodies against either protein shows that the two proteins interact with each other, and thus p38 is named unrip (unr–interacting protein). Recombinant unr acts synergistically with recombinant PTB to stimulate translation dependent on the rhinovirus IRES. In contrast, unr did not significantly augment the PTB-dependent stimulation of poliovirus IRES activity.